Relationship between Dietary Oxalate Intake and Urinary Oxalate Excretion in Patients with Nephrolithiasis : A Systematic Review - Yuni Agnes Lubis; Dini Miori; Heri Setiawan (The International Journal of Medical Science and Health Research, 2026)
Introduction: Nephrolithiasis, particularly calcium oxalate (CaOx) stones, is strongly influenced by urinary oxalate excretion. Dietary oxalate intake is a modifiable risk factor, but its quantitative relationship with urinary oxalate and the comparative effectiveness of dietary strategies remain debated. This systematic review evaluates the positive significant relationship between dietary oxalate intake and urinary oxalate excretion in nephrolithiasis patients. Methods: A systematic search was performed for human studies assessing both dietary oxalate intake and urinary oxalate excretion in nephrolithiasis patients. Data on study design, dietary assessment, urinary oxalate measurement, intervention effects, and confounding factors were extracted. Results: The foundational quantitative estimate shows that for every 100 mg of dietary oxalate consumed, urinary oxalate increases by approximately 2.7 mg (1). Dietary oxalate accounts for 25-53% of total urinary oxalate (2). Low-oxalate dietary interventions significantly reduce urinary oxalate by 20-35% in idiopathic hyperoxaluria (3-5). In the prospective randomized trial by Gupta et al., low-oxalate diet reduced urinary oxalate by 31.1% (P=0.007) (3). Aziz et al. reported a 48.9% reduction (23). Normal-calcium, low-protein, low-salt diet reduced oxaluria by 78 µmol/day (95% CI 26.48-129.52) and stone recurrence (RR 0.77) (30). Dietary counseling significantly lowered urinary oxalate from 46.28 to 32.56 mg/day (P<0.0001) (6). Mediterranean diet adherence was associated with 13-41% lower stone risk (pooled HR 0.72, 95% CI 0.59-0.87) despite higher urinary oxalate (16). Calcium intake with meals significantly reduces urinary oxalate (7,25), while ascorbic acid supplementation increases urinary oxalate by 20-33% (12,21). Enteric hyperoxaluria shows attenuated response to dietary restriction alone (8,9). Discussion: A consistent positive association exists between dietary oxalate and urinary oxalate, with significant reductions from low-oxalate diets. However, multi-component dietary patterns (DASH, Mediterranean) may provide superior overall lithogenic risk reduction by improving citrate, magnesium, and urine volume. Conclusion: Dietary oxalate restriction significantly reduces urinary oxalate in idiopathic hyperoxaluria. Meal-concurrent calcium intake and comprehensive dietary patterns are more effective than oxalate restriction alone. Enteric hyperoxaluria requires additional therapies.